KONTEKTUALITAS DESAIN FASAD GEDUNG MCHCC RS HASAN SADIKIN PADA KAWASAN CAGAR BUDAYA - Naufaly, Lulu; Subekti, Bambang (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2024)
The Mother and Child Service Center Building at Hasan Sadikin Hospital Bandung is one of the new service center buildingsalocated inathe Cultural Heritage Area of the City of Bandung. Inaorderatoamaintainathe sustainability, harmony, and harmonization of the area, special studies and attention are needed. Facade element design is a benchmark for harmonizing new buildings in historic cultural heritage areas. By using the contextual architecture approach, this facade design study was carried out. The study method uses descriptive qualitative analysis, namely understanding and describing phenomena or events in detail and depth. Thearesultssofatheaanalysisashowathat conversion activities in the Hasan Sadikin Hospital area need toibeicontinuouslyiimproved by increasing cooperation betweenatheagovernment, managementaorganizations, areas, and buildingaowners. The construction of the building for the mother and child service center building, Hasan Sadikin Hospital, Bandung, although it is quite far from the cultural heritage building, is included in the cultural heritage area, which means that theafacadeiofitheibuildingiis madeias harmonious as possible with the surrounding environment. It was proposed that the facade of the MCHC building be in harmony with the surrounding buildings by displaying details or ornaments taken from cultural heritage buildings and applied to the new building facades.